Advancements in research on the immune-inflammatory mechanisms mediated by NLRP3 inflammasome in ischemic stroke and the regulatory role of natural plant products - Yang, Kailin; Zeng, Liuting; He, Qi; Wang, Shanshan; Xu, Hao; Ge, Jinwen (Frontiers in Pharmacology, 2024)
Ischemic stroke (IS) is a major cause of mortality and disability among adults. Recanalization of blood vessels to facilitate timely reperfusion is the primary clinical approach; however, reperfusion itself may trigger cerebral ischemia-reperfusion injury. Emerging evidence strongly implicates the NLRP3 inflammasome as a potential therapeutic target, playing a key role in cerebral ischemia and reperfusion injury. The aberrant expression and function of NLRP3 inflammasome-mediated inflammation in cerebral ischemia have garnered considerable attention as a recent research focus. Accordingly, this review provides a comprehensive summary of the signaling pathways, pathological mechanisms, and intricate interactions involving NLRP3 inflammasomes in cerebral ischemia-reperfusion injury. Moreover, notable progress has been made in investigating the impact of natural plant products (e.g., Proanthocyanidins, methylliensinine, salidroside, α-asarone, acacia, curcumin, morin, ginsenoside Rd, paeoniflorin, breviscapine, sulforaphane, etc.) on regulating cerebral ischemia and reperfusion by modulating the NLRP3 inflammasome and mitigating the release of inflammatory cytokines. These findings aim to present novel insights that could contribute to the prevention and treatment of cerebral ischemia and reperfusion injury.